Renal Cell Carcinoma - López, José I. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Renal cancer is a health problem of major concern worldwide. Although tyrosine kinase inhibitors and immune check-point blockade treatments, alone or in combination, are giving promising results, failures are quite frequent due to intratumor heterogeneity and to the acquisition of drug resistance. The spectrum of renal cell carcinoma subtypes is wide. Up to 70-80% of renal tumors are clear cell renal cell carcinomas, a clinically aggressive tumor subtype linked to VHL gene inactivation. Next in frequency, the papillary renal cell carcinoma category encompasses an intricate puzzle of classic and newly described entities with poorly defined limits, some of them pending definite clarification. Likewise, the chromophobe-oncocytoma duality, the so-called hybrid tumors and oncocytic neoplasms, remain to be well profiled. Finally, a growing list of very uncommon renal tumors linked to specific molecular signatures fulfill the current portrait of renal cell neoplasia. This Special Issue of Cancers regards RCC from very different perspectives, from the intimate basic mechanisms governing this disease to the clinical practice principles of their diagnoses and treatments. The interested reader will have the opportunity to contact with some of the most recent findings and will be updated with excellent reviews.